Sistem Pompa Air Otomatis Berbasis Arduino Uno Untuk Optimalisasi Penyiraman Tanaman Menggunakan Sensor Soil Moisture - Sigit Prakosa Adhi Nugraha; Yohanes Tri Novia Putra; Rizal Agri Wahyuadi; Raka Dian Mahardi; Muhammad ‘Atiq; Danang Hendrawan (Jurnal Sains dan Ilmu Terapan, 2024)
An automatic plant watering system employing the Arduino Uno was developed to optimize water usage in agriculture. This system utilizes a soil moisture sensor to assess soil moisture levels and regulate the water pump automatically via a relay.The objective of this research is to devise a system that is efficient, reduces superfluous water usage, and ensures adequate moisture for plants. The experimental results demonstrate the system's capacity to adjust the watering schedule of plants in accordance with soil moisture conditions, exhibiting a rapid response time and minimal energy consumption.